2016
DOI: 10.1007/978-3-319-39357-5
|View full text |Cite
|
Sign up to set email alerts
|

IEA International Civic and Citizenship Education Study 2016 Assessment Framework

Abstract: duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. indicated otherwise in the credit line; if such material is not included in the works Creative Commons license and the respective action is not permitted by statutory regulation, users will need to obtain permission from the license holder to duplicate, adapt or reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
0
40

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 125 publications
2
203
0
40
Order By: Relevance
“…In addition, the students' participation in school and society was assessed along with their perceptions of the school climate (cf. Schulz et al 2008). The students were asked if they participated (yes/no) in societal activities such as scouting, multicultural organizations, human rights organizations, environmental organizations, the youth section of a political party, religious communities or volunteer work.…”
Section: Student Backgrounds Participation In School/society and Permentioning
confidence: 99%
“…In addition, the students' participation in school and society was assessed along with their perceptions of the school climate (cf. Schulz et al 2008). The students were asked if they participated (yes/no) in societal activities such as scouting, multicultural organizations, human rights organizations, environmental organizations, the youth section of a political party, religious communities or volunteer work.…”
Section: Student Backgrounds Participation In School/society and Permentioning
confidence: 99%
“…Indeed, research on moral education has shown that classroom discussion on moral dilemmas can enhance students' levels of moral reasoning (Berkowitz et al 2008;Blatt and Kohlberg 1975;Nucci, Creane, and Powers 2015). In addition, there is a substantial body of literature that indicates that a classroom climate in which students feel encouraged to openly discuss political and social issues promotes civic knowledge (Schulz et al 2010;Torney-Purta 2002) and civic participation (Godfrey and Grayman 2014;Torney-Purta 2002), via an enhanced belief in their self-efficacy with regard to civic participation (Manganelli, Lucidi, and Alivernini 2015).…”
Section: Classroom Discussion In the Context Of Democratic Citizenshmentioning
confidence: 99%
“…The scales were transformed to have an international average of 50 and a standard deviation of 10 (these values were slightly different in our study because we used a subsample of 22 countries). For more details see Schulz et al (2011). A detailed list of all items can be found in Appendix 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although the ERM was administered in 24 European countries, we used a subset of 22 countries that were members of the European Union at the time of data collection 1 . The sampling design ensured that samples were representative of the participating countries and sampled one classroom per school (Schulz, Ainley, & Fraillon, 2011). The data have a hierarchical structure with 71,282 eighth-graders (level 1) who were nested in 3,632 classrooms (level 2; M classroom size = 19.62) that were nested in 22 countries (level 3).…”
Section: Participants and Proceduresmentioning
confidence: 99%